Sharp Minima for Multiobjective Optimization in Banach Spaces - Zheng, X.; Yang, X.; Teo, Kok Lay (Springer, 2006)
We study sharp minima for multiobjective optimization problems. In terms of the Mordukhovich coderivative and the normal cone, we present sufficient and or necessary conditions for existence of such sharp minima, some of which are new even in the single objective setting.